Diagnosis of the nutritional status of the Weight Lifting Permanent Olympic Team athletes of the Brazilian Olympic Committee (COB) - Cabral, C. A. C.; Rosado, G. P.; Silva, C. H. O.; Marins, J. C. B. (Revista Brasileira de Medicina do Esporte, 2006)
This study aimed to diagnose the nutritional status of the Weight Lifting Permanent Olympic Team Athletes of the Brazilian Olympic Committee (COB). The sample was composed of 24 athletes, aged 16-23 yr, 12 males (19.7 ± 2.4 yr) and 12 females (19.2 ± 1.8 yr). The following procedure was applied to diagnose the nutritional status: analysis of the adequability of energy and macronutrient intake - carbohydrates (CHO), lipids (LIP) and proteins (PRO) -, through the methods 24-hr diet records and the Food Consumption Frequency Questionnaire, besides anthropometrical profile characterization. The results obtained from the dietary evaluation showed that the energy distribution among the macronutrients was adequate, 54 ± 6.8% (CHO); 28,5 ± 5.9% (LIP); and 14.5 ± 3.4% (PRO) for the male team, and 56.3 ± 4.7% (CHO); 28.6 ± 4.6% (LIP); and 13.7 ± 2.4% (PRO) for the female team. However, regarding total energy intake, 83% of the athletes presented energy intake below the recommended values, considering the high level of physical activity, resulting in daily caloric deficiency. Body fat percentage of the male athletes (3.6 ± 0.7%) indicated that all of them were below the reference standard, while 58% of the female athletes had excess fat (17.9 ± 5.8%). It was concluded that although the athletes showed an adequate caloric distribution of macronutrients, it was still not sufficient to meet the energy requirements of their modality, thus these athletes should seek nutritional orientation.